2014
DOI: 10.1007/s10120-014-0436-1
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of surgeon specialization on survival for gastric cancer patients after surgery with curative intent

Abstract: Background Many studies have affirmed the survival benefit for cancer patients treated by specialized surgeons. Methods A total of 967 patients with gastric cancer (GC) who underwent gastrectomy with curative intent in our center were enrolled. Patients were categorized into two groups based on surgeon specialization: the specialized group (SG) and nonspecialized group (NSG). To overcome bias due to the different distribution of covariates for the two groups, a one-to-one match was applied using propensity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
4
11
1
Order By: Relevance
“…Several previous studies have demonstrated an influence of surgeon volume on postoperative outcomes among patients undergoing elective and emergent surgery [13,24]. With regard to gastric cancer surgery, patients treated by high-volume and experienced surgeons have definitively better short-and long-term outcomes [25,26]. Our data shows that both hospital and surgeon volume were associated with morbidity and mortality after gastrectomy.…”
Section: Discussionsupporting
confidence: 50%
“…Several previous studies have demonstrated an influence of surgeon volume on postoperative outcomes among patients undergoing elective and emergent surgery [13,24]. With regard to gastric cancer surgery, patients treated by high-volume and experienced surgeons have definitively better short-and long-term outcomes [25,26]. Our data shows that both hospital and surgeon volume were associated with morbidity and mortality after gastrectomy.…”
Section: Discussionsupporting
confidence: 50%
“…Our findings differ from the study by Ramirez et al13 First, there is a growing consensus in the literature that enhanced surgical technique and rich experience can improve survival outcomes of various types of malignancies 17,18. We noticed that in the trial by Ramirez et al, the participating sites were required to submit perioperative outcomes from a minimum of any 10 minimally invasive surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study confirmed that overall recurrence rate of the “D2 plus” group, especially LNs recurrence was lower than that of the D2 group. This was consistent with the results of the previous studies 3,26 . We believe that distal GC with these LNs metastasis is at local advanced stage, rather than systemic disease.…”
Section: Discussionsupporting
confidence: 94%